Effects of PVA coated nanoparticles on human immune cells - Strehl C (Dove Medical Press, 2015)
Cindy Strehl,1,2 Timo Gaber,1–3 Lionel Maurizi,4 Martin Hahne,1,2 Roman Rauch,1,2 Paula Hoff,1–3 Thomas Häupl,1 Margarethe Hofmann-Amtenbrink,5 A Robin Poole,6 Heinrich Hofmann,4 Frank Buttgereit1–3 1Department of Rheumatology and Clinical Immunology, Charité Universitätsmedizin Berlin, Berlin, Germany; 2German Rheumatism Research Centre (DRFZ), Berlin, Germany; 3Berlin-Brandenburg Center for Regenerative Therapies (BCRT), Berlin, Germany; 4Powder Technology Laboratory, Ecole Polytechnique Federale de Lausanne (EPFL), Lausanne, Switzerland; 5MatSearch Consulting Hofmann, Pully-Lausanne, Switzerland; 6Department of Surgery, McGill University, Montreal, QC, Canada Abstract: Nanotechnology provides new opportunities in human medicine, mainly for diagnostic and therapeutic purposes. The autoimmune disease rheumatoid arthritis (RA) is often diagnosed after irreversible joint structural damage has occurred. There is an urgent need for a very early diagnosis of RA, which can be achieved by more sensitive imaging methods. Superparamagnetic iron oxide nanoparticles (SPION) are already used in medicine and therefore represent a promising tool for early diagnosis of RA. The focus of our work was to investigate any potentially negative effects resulting from the interactions of newly developed amino-functionalized amino-polyvinyl alcohol coated (a-PVA) SPION (a-PVA-SPION), that are used for imaging, with human immune cells. We analyzed the influence of a-PVA-SPION with regard to cell survival and cell activation in human whole blood in general, and in human monocytes and macrophages representative of professional phagocytes, using flow cytometry, multiplex suspension array, and transmission electron microscopy. We found no effect of a-PVA-SPION on the viability of human immune cells, but cytokine secretion was affected. We further demonstrated that the percentage of viable macrophages increased on exposure to a-PVA-SPION. This effect was even stronger when a-PVA-SPION were added very early in the differentiation process. Additionally, transmission electron microscopy analysis revealed that both monocytes and macrophages are able to endocytose a-PVA-SPION. Our findings demonstrate an interaction between human immune cells and a-PVA-SPION which needs to be taken into account when considering the use of a-PVA-SPION in human medicine. Keywords: nanoparticle, cell viability, cytokine, monocyte, macrophage